Evaluation of hover types with and without supplemental heat for finishing pig performance - G L Allee; David A Nichols; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1979)
One hundred sixty Yorkshire barrows and gilts were used to evaluate supplemental heat and various types of hovers for finishing pigs during December, 1978, and January, 1979. Hovers constructed of plywood, straw, and plywood covered with foil were placed over pens with and without catalytic heaters to determine the effect of each on performance. Hovers modified the pig's environment by an average of 80 straw hover, 90 foil covered plywood, and 30 plywood hover. Average daily gain and feed required per pound of gain were similar for all treatments. Pigs fed in pens with catalytic heaters gained slightly faster and were 5% more efficient than pigs fed in pens without heaters.; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; Hover types; Supplemental heat; Finishing pig performance